2020
DOI: 10.1177/2516103220987227
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress, burnout and compassion satisfaction among Flemish foster care workers during the COVID-19 lockdown

Abstract: This study examines secondary traumatic stress (STS), burnout and compassion satisfaction (CS) in Flemish foster care workers (FCW) during the COVID-19 lockdown. Even though child welfare workers are at increased risk for STS and burnout, these constructs have not been studied in FCW so far. Additionally, the COVID-19 measures severely impacted Flemish FCW’s work, personal and client environment, possibly stimulating the onset of STS and burnout and weakening CS. Moreover, this study aims to identify the work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…worries about COVID-19, family conflict) were negative predictors for STS and BO among professionals from a foster-care system (Whitt-Woosley et al, 2022 ). Similarly, fear of COVID-19 contamination for household members was also associated with STS and BO (but not CS) among foster-care workers in Belgium (Verheyden et al, 2020 ). In response to the rapidly changing pandemic situation, adjustments in organizational practices may bring additional stressors to frontline healthcare workers.…”
Section: Discussionmentioning
confidence: 96%
“…worries about COVID-19, family conflict) were negative predictors for STS and BO among professionals from a foster-care system (Whitt-Woosley et al, 2022 ). Similarly, fear of COVID-19 contamination for household members was also associated with STS and BO (but not CS) among foster-care workers in Belgium (Verheyden et al, 2020 ). In response to the rapidly changing pandemic situation, adjustments in organizational practices may bring additional stressors to frontline healthcare workers.…”
Section: Discussionmentioning
confidence: 96%
“…In some countries, professionals serving in foster care are called 'child welfare workers' (Lindahl & Bruhn, 2018) or 'case workers' (Chambers et al, 2020), whereas in Belgium and the Netherlands, the term 'foster care workers' is preferred (Verheyden et al, 2020). In the Netherlands, until 1995, supporting foster families was one of the many tasks of a social worker.…”
Section: Context and Responsibilities Of Dutch Foster Care Workersmentioning
confidence: 99%
“…A systematic review of DV during the COVID-19 pandemic [5] revealed that home lockdown left the victims more exposed to their perpetrators, occasioning increased violence and diminished reports. A study conducted in Portugal [6] showed that in a sample of 1062 participants, 13.7% (n = 146) stated that they had suffered DV during the pandemic. Most victims were subjected to psychological violence (13.0%, n = 138), with 1.0% (n = 11) and 0.9% (n = 10), respectively, exposed to sexual and physical violence.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, child protective and residential foster care services felt the impact of the restrictions on their functioning, with professionals expressing that they were subjected to additional duties and further stress [12]. Secondary traumatic stress, burnout, and compassion satisfaction in foster care workers during the COVID-19 lockdown were identified [13].…”
Section: Introductionmentioning
confidence: 99%